Developmental Mechanisms in Articular Cartilage Degradation in Osteoarthritis - Tchetina, Elena V. (Hindawi Publishing Corporation, 2011)
Osteoarthritis is the most common arthritic condition, which involves progressive degeneration of articular cartilage. The most recent accomplishments have significantly advanced our understanding on the mechanisms of the disease development and progression. The most intriguing is the growing evidence indicating that extracellular matrix destruction in osteoarthritic articular cartilage resembles that in the hypertrophic zone of fetal growth plate during endochondral ossification. This suggests common regulatory mechanisms of matrix degradation in OA and in the development and can provide new approaches for the treatment of the disease by targeting reparation of chondrocyte phenotype.